Is The Captain of the Men of Death Still At Play? Long-Run Impacts of Early Life Pneumonia Exposure during Sulfa Drug Revolution in America - Sonia Bhalotra; Atheendar Venkataramani (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
We exploit the introduction of sulfa drugs in 1937 to identify the impact of exposure to pneumonia in infancy on later life well-being and productivity in the United States. Using census data from 1980-2000, we find that cohorts born after the introduction of sulfa experienced increases in schooling, income, and the probability of employment, and reductions in disability rates. These improvements were larger for those born in states with higher pre-intervention pneumonia mortality rates, the areas that benefited most from the availability of sulfa drugs. Men and women show similar improvements on most indicators but the estimates for men are more persistently robust to the inclusion of birth state specific time trends. With the exception of cognitive disabilities for men and, in some specifications, work disability for men and family income, estimates for African Americans tend to be smaller and less precisely estimated than those for whites. Since African Americans exhibit larger absolute reductions in pneumonia mortality after the arrival of sulfa, we suggest that the absence of consistent discernible long run benefits may reflect barriers they encountered in translating improved endowments into gains in education and employment in the pre- Civil Rights Era.
Keywords: I18; H41; 330; early childhood; infectious diseases; pneumonia; medical innovation; antibiotics; schooling; income; disability; mortality trends